First fluctuation measurements using an Imaging Neutral Particle Analyzer on DIII-D - K.R. Gage; X.D. Du; W.W. Heidbrink; J. Gonzalez-Martin; D. Liu; A.C. Brown (Nuclear Fusion)
A recent upgrade to the Imaging Neutral Particle Analyzer (INPA) on DIII-D has allowed for the first fluctuation measurements using an INPA to be taken during a neoclassical tearing mode (NTM). The INPA signal tracked the mode over 150 ms as the mode frequency dropped to zero, capturing both the NTM with poloidal and toroidal mode numbers $m/n = 2/1$ and a $3/2$ mode at double the frequency. Analysis shows that the signals originate from charge exchange events near the edge of the plasma, and relative fluctuation amplitudes are greater than 25% for the duration of the NTM. Filtered signals show frequency beating patterns that are phase-space dependent. Simulated signal is dominated by prompt transport from the neutral beams to the INPA sightline, while the contribution from the slowing down distribution is significantly lower. Simulated measurements in the range of pitches that the diagnostic is sensitive to ( $0.5\unicode{x2A7D} \left| \frac{v_{\parallel}}{v} \right| \unicode{x2A7D} 0.75$ ) show the signal is dominated by trapped orbits that pass through magnetic islands near the edge of the plasma. Calculations of expected fluctuation levels show that only direct interaction with the NTM can provide the strong relative fluctuation levels seen experimentally. The prompt nature of the orbits and thin radial layer found to contribute to synthetic signals suggest INPA passive data may be used to measure the perturbations of confined orbits on a single pass through a plasma instability.